Poststroke fever etiology - Lijiang Wang; Wei Jin; Yuhua Wu; Menglu Zhu (Medicine, 2026)
Rationale: Piperacillin–tazobactam is a widely used antibiotic, but its adverse effects, particularly drug fever and hematological toxicities, are often underestimated. The concurrent occurrence of drug fever and agranulocytosis may complicate the differential diagnosis of persistent or recurrent fever, particularly in patients with stroke-associated pneumonia. We report a case of probable piperacillin–tazobactam–associated drug fever and agranulocytosis and review the relevant literature. Patient concerns: A 45-year-old woman with cerebral infarction complicated by stroke-associated pneumonia received prolonged piperacillin–tazobactam therapy. During continued treatment, she developed recurrent high fever accompanied by a progressive decline in neutrophil count, with an absolute neutrophil count nadir of 0.3 × 10 9 /L. Diagnoses: After systematic evaluation of infectious and noninfectious causes, the patient was considered to have probable piperacillin–tazobactam–associated drug fever and agranulocytosis. A Naranjo Adverse Drug Reaction Probability Scale score of 7 supported a probable association between piperacillin–tazobactam exposure and the observed adverse events. Interventions: Piperacillin–tazobactam was discontinued. Granulocyte-supportive treatment, including granulocyte colony-stimulating factor, was administered, and the antimicrobial regimen was adjusted to address the possibility of concurrent or secondary infection. Outcomes: Following discontinuation of piperacillin–tazobactam, granulocyte-supportive treatment, and antimicrobial adjustment, the patient’s fever resolved and the neutrophil count gradually recovered. She was discharged in stable clinical condition, and no recurrence of fever was reported during follow-up for up to 1 year. Lessons: In patients receiving prolonged piperacillin–tazobactam therapy, recurrent or persistent fever accompanied by a declining neutrophil count should raise suspicion for drug fever and hematological toxicity. Serial blood-cell monitoring and careful evaluation of the temporal relationship between drug exposure and clinical manifestations are important for early recognition. However, infectious and other noninfectious etiologies should be systematically evaluated before attributing these findings to piperacillin–tazobactam, and causality should be interpreted cautiously when multiple therapeutic interventions are performed concurrently.